Infinite symmetries in the Skyrme model - Ferreira, L. A.; Guillen, J. S. (Elsevier B.V., 2001)
We show that the Skyrme theory possesses a submodel with an infinite number of local conserved currents. The constraints leading to the submodel explore a decomposition of SU(2) with a complex field parametrizing the symmetric space SU(2)/U(1) and a real field in the direction of U(1). We demonstrate that the Skyrmions of topological charges ii belong to such integrable sector of the theory. Our results open ways to the development of exact methods, compensating for the non-existence of a BPS type sector in the Skyrme theory. (C) 2001 Published by Elsevier B.V. B.V.